Delamination monitoring of honeycomb composite for aircraft structure using Fiber Bragg Gratings / Ramzyzan Ramly - Ramly, Ramzyzan (Institute of Graduate Studies, UiTM, 2015)
Since two decades ago, non-metallic composites especially honeycomb core sandwich panel were widely used in the secondary non-controlling surfaces such as the horizontal and vertical stabilizer main boxes. One of the problems in honeycomb sandwich structure is detection of delamination between the core and the skin. In order to overcome this problem, most aircraft manufacturers equipped their aircrafts with Health Monitoring System (HMS) in place to monitor the status of the aircraft structural integrity. There are many types of HMS being adopted by the aircraft manufacturers. The type of HMS being studied in this research is the one using Fiber Bragg Grating (FBG) system, which utilize optical strain sensor using light wave as the means of signal detection. The objectives of this research are to detect the location of delamination in sandwich panel and to determine the extents or the relative size of the delamination using FBG. In this study, an FBG sensor array was embedded in the honeycomb core carbon fiber skin sandwich panel. The sandwich panel was fabricated in accordance to the aviation industry standards process as well as the materials used in fabrication…